Russel Botman A Tribute 1953-2014 - Grundlingh, Albert (African Sun Media, 2017)
This celebratory volume tells the story of the late Russel Hayman Botman who died suddenly early in his second term as Rector and Vice-Chancellor of Stellenbosch University. Botman's story is told from his earliest childhood years until his last day as rector. The nature of tributes and celebratory volumes is that it can never be exhaustive. It tells a rich story from limited perspectives. It, however, serves as invitation, stimulus and inspiration to others connected to Botman to also tell their stories about his story.